Tuning Corrosion Resistance and AC Soft Magnetic Properties of Fe-Co-Ni-Al Medium-Entropy Alloy via Ni Content - Wenfeng Peng; Yubing Xia; Hui Xu; Xiaohua Tan (Entropy)
Corrosion of soft magnetic materials during service can significantly impact their performance and service life, therefore it is important to improve their corrosion resistance. In this paper, the corrosion resistance, alternating current soft magnetic properties (AC SMPs) and microstructure of FeCoNixAl (x = 1.0–2.0) medium-entropy alloys (MEAs) were studied. Corrosion resistance is greatly improved with an increase in Ni content. The x = 2.0 alloy has the lowest corrosion current density (Icorr = 2.67 × 10−7 A/cm2), which is reduced by 71% compared to the x = 1.0 alloy. Increasing the Ni content can improve the AC SMPs of the alloy. When x = 1.75, the total loss (Ps) is improved by 6% compared to the x = 1.0 alloy. X-ray diffraction (XRD) and scanning electron microscopy (SEM) show that the increase in Ni content is beneficial for promoting the formation of the face-centered-cubic (FCC) phase, and the body-centered-cubic (BCC) phase is gradually divided by the FCC phase. Electron backscatter diffraction (EBSD) shows that, with the increase in Ni content, the number of grain boundaries in the alloy is greatly reduced and numerous phase boundaries appear in the alloys. The degree of strain concentration is significantly reduced with the increasing Ni content. The corrosion mechanism of alloys is also discussed in this paper. Our study provides a method to balance the soft magnetic properties and corrosion resistance, paving the way for potential applications of Fe-Co-Ni-Al MEAs in corrosive environments.